An Effective Strategy for Interface Modification and Polysulfide Confinement by Gel Polymer Electrolyte Coating on the Sulfur Cathode. Issue 10 (24th June 2020) - Yuan, Yan; Zheng, Dongdong; Lu, Hai; Li, Zhengqian; Dang, Yangyang; Fang, Zhao
Abstract : A novel poly(acrylamide-co-acrylic acid) (P(AM-co-AA)) coating layer is facilely introduced on the top of sulfur composite cathode. The polymer membrane owns abundant and well-distributed microporous framework, favoring large electrolyte uptake and high ionic conductivity. Upon activation with the liquid electrolyte, the porous matrix immediately swells, forming a gel polymer electrolyte coating (GPEC) cathode. Not only does the unique coating design greatly restrain the out-diffusion of polysulfides from the cathode, but also improves ion transport at the cathode/electrolyte interface and provides flexible surface protection for the electrode structure. The GPEC cathode exhibits relatively low polarization, high sulfur utilization and superior cycle stability, as compared to the conventional sulfur cathode.